Training Treatment Skill of Children Abuse Victims for College Students - Koesdyantho, Agustinus Roedy; Koesdyantho, Agustinus Roedy (International Journal of Community Service Learning, 2021)
Child abuse is a serious phenomenon that needs treatment to recover the victims. The present article aims at describing a training of giving treatments to recover children as victims from abuse and violence to show the students’ (participants) knowledge and service before they do internship program at an orphanage. The subject of research is 7th semester students of guidance and counseling program at Universitas Slamet Riyadi, Indonesia. The result of the research are the improvements of the college students’ knowledge and service in giving treatment for child abuse victims; they are familiar with six forms of treatment to recover the victims that consist of Combined Parent-Child Cognitive Behavioral Therapy (CPC-CBT), Parent Training and Multi-systemic Therapy, Project Support (Children’s Protective Services), Web-based parenting skills, Home Visiting Program, and School Based Mental Health Intervention for Children. The conclusion of the article is treatments in the form of collaboration between parents (caregivers), schools, and children (as victims) to recover child abuse and violence through a variety of phases to realize the purposes and children abuse as victims need appropriate treatment based on the condition of them and such six treatments as a choice and solution to recover the victims.